Predictors of traffic events due to hypoglycemia in adults with type 1 diabetes: A Brazilian prospective cohort study. (August 2021) - Fenalti Salla, Rafaela; de David, Julia; Schneider, Larissa; Tschiedel, Balduino; Teló, Gabriela H.; Schaan, Beatriz D.
Abstract: Background: Individuals with type 1 diabetes (T1D) are exposed to an elevated risk of automobile accidents especially because of hypoglycemia that impairs physiological and defense responses. Objectives: To assess local risk factors for traffic events in T1D adult Brazilian patients. Methods: This is a prospective study and 12-month follow-up to assess predictors for traffic events on a cohort of drivers with T1D (n = 168) in Brazil. The inclusion criteria for participants were Brazilian nationality, age ≥ 18 years-old, diagnosis of T1D for more than one year, driving license B, C or D categories (four-wheel vehicles), driving three-times per week or more, and checking blood glucose twice-daily or more. The primary outcome was hypoglycemia driving mishaps assessed by a seven-query questionnaire about the past 30 days. Secondary outcomes included driving mishaps not related to hypoglycemia. Statistical analysis was performed through Poisson regression models with robust variance estimarion, in which the measure of association is the relative risk. Results: A total of 109 participants completed the 12-month follow-up. Most of them were men (66%) and 37 ± 11 years-old, and had a mean HbA1c of 8.2% (66 mmol/mol). In the follow up, the incidence of traffic events was high (70.6%); however, only a minority was attributed to hypoglycemia as the cause of the reported event (19.3%). The best predictors for new traffic events due to hypoglycemia were those related to driving characteristics. The best of them was a history of episodes of hypoglycemia while driving [RR 3.40 (1.22–9.43); p < 0.05]. Conclusions: We found that previous episodes of hypoglycemia while driving significantly increase the risk of new traffic events and are the best predictor for it. This highlights the need to assess the risks of traffic accidents especially in people who have had experienced episodes of hypoglycemia while driving.